1995
DOI: 10.1161/01.cir.91.7.2028
|View full text |Cite
|
Sign up to set email alerts
|

Blade Balloon Atrial Septostomy in Patients With Severe Primary Pulmonary Hypertension

Abstract: Blade balloon atrial septostomy resulted in clinical and hemodynamic improvement and improved survival in selected patients with severe primary pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
147
1
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(161 citation statements)
references
References 14 publications
5
147
1
8
Order By: Relevance
“…Our study series provides the longest follow-up of patients with AS in the setting of PAH and, as in other study series [5,7,27], AS significantly improved long-term survival in these patients. AS improved haemodynamic parameters that correlate with survival (cardiac index and right ventricular filling pressures) and 6MWT, another surrogate of survival in PAH, and this may explain the impact of the procedure on shortterm survival.…”
Section: Effect Of As On Long-term Survivalsupporting
confidence: 74%
See 3 more Smart Citations
“…Our study series provides the longest follow-up of patients with AS in the setting of PAH and, as in other study series [5,7,27], AS significantly improved long-term survival in these patients. AS improved haemodynamic parameters that correlate with survival (cardiac index and right ventricular filling pressures) and 6MWT, another surrogate of survival in PAH, and this may explain the impact of the procedure on shortterm survival.…”
Section: Effect Of As On Long-term Survivalsupporting
confidence: 74%
“…In most reported series [5,[7][8][9][10][11], AS has been performed only after the failure of different PAH-specific pharmacological interventions. In the present study, patients with concomitant pharmacological treatment had AS performed before pharmacological treatment was initiated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in children with iPAH has demonstrated a significant long-lasting benefit with clinical, haemodynamic and survival advantage following blade-balloon atrial septostomy. 102 In adults, a large series is reported by Sandoval and colleagues from Mexico. 103 The atrial septum is first punctured percutaneously.…”
Section: Balloon Atrial Septostomymentioning
confidence: 99%